THE REPRESENTATION OFVICTIMS AND PERPETRATORSIN GALAMEDIA :A Critical Analysis of Sexual Violence against Women - Susanti Kartini, - (2008)
The present study is entitled "The Representation of Victims and Perpetrators in Galamedia : A Critical Analysis of Sexual Violence against Women". This study aims to find how the victims and the perpetrators are represented in texts and to examine the ideology behind the representation. This study employs critical discourse analysis (CDA) as the analytical framework. Purposive sampling was used in collecting the data. The data included two articles taken from a column named "Malu-maluin" in a local newspaper Galamedia. The data are analyzed using three stages ofanalysis, whose approach is proposed by Fairclough (1995). The stages include the description stage, the interpretation stage, and the explanation stage. This study focuses on the analysis ofthematization, transitivity, passivization, and lexical choice. The findingsteveallhat the texts that Galamedia produced tend to marginalize the female victims. As the passive participants, the victims are presented powerless. Moreover, there is a responsibility shifting from the perpetrators to the victims. The victims are presented as the agents of their own victimization. Meanwhile, the perpetrators are presented as the powerful participants. However, the perpetrators tend to be hidden from the readers' attention. The overall description of the victims and the perpetrators show that patriarchal ideology gets articulated in the texts. This ideology appears to control Galamedia inorganizing the texts in such a way.